2011
DOI: 10.1111/j.1365-2133.2011.10493.x
|View full text |Cite
|
Sign up to set email alerts
|

Merkel cell carcinoma in Western Australia: a population-based study of incidence and survival

Abstract: Incidence of MCC in WA is the highest reported in the literature. In addition, MCC has worse survival than melanoma. The high rates and demographic and anatomical distribution are consistent with sun exposure playing a causal role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
66
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 24 publications
14
66
0
4
Order By: Relevance
“…It increased from 1980 to 2000 in US and in Europe [4][5][6][7]. This can be related to a true increased incidence by itself or caused by ageing of the population, increased sun exposure and/or improvement of diagnostic immunohistochemical tools as well as improved registration.…”
Section: Epidemiology and Aetiologymentioning
confidence: 95%
“…It increased from 1980 to 2000 in US and in Europe [4][5][6][7]. This can be related to a true increased incidence by itself or caused by ageing of the population, increased sun exposure and/or improvement of diagnostic immunohistochemical tools as well as improved registration.…”
Section: Epidemiology and Aetiologymentioning
confidence: 95%
“…A predominantly viral etiology appears likely given that a human pathogen called Merkel cell polyomavirus (MCPyV; Feng et al, 2008;Spurgeon and Lambert, 2013) has been discovered in up to 90% of cases in North America and Europe (Donepudi et al, 2012;Prieto Munoz et al, 2013). However, there has been some speculation that sun exposure may generate a greater contribution to the incidence of MCC in parts of Australia because of elevated levels of ambient UV radiation (Girschik et al, 2011). Our recent finding (Youlden et al, 2014) that the incidence rate of MCC is twice as high in Queensland than anywhere else in the world and up to seven times higher than rates in some countries in northern Europe may provide support for the hypothesis that a larger proportion of MCCs in Australia are sun related.…”
Section: Introductionmentioning
confidence: 85%
“…Data pertaining to the epidemiology of MCC have not been studied extensively. However, a cancer registry from Western Australia between 1993 and 2007 indicated that this region had the highest reported incidence of MCC in the world [ 38 ]. Males were found to be affected more commonly than females-1 per 100,000 in males compared to 0.63 per 100,000 in females, with the median age being 77 years [ 38 ].…”
Section: Other Cutaneous Malignancies Of the Head And Neckmentioning
confidence: 98%